THE ROLE OF STORY TELLING ON THE DEVELOPMENT OF RELIGIOUS VALUES IN GROUP B TK ALKHAIRAAT TONDO MANTIKULORE DISTRICT - Nurhayati; Angraeni A; Ramli (Education Journal, 2021)
The purpose of the study was to determine the application of story telling, to determine the development of religious values, and to determine the role of story telling on the development of religious values ​​in group B of TK Alkhairaat Tondo Kec. Mantikulore. The formulation of the problem in the research is how to apply story telling, how to develop religious values, and how is the role of story telling to the development of religious values ​​in group B TK Alkhairaat Tondo Kec. Mantikulore. The research method is a qualitative research. descriptive research subjects totaled 15 children. Data were collected through observation sheets and documentation. The results of the fourth week of the study of 15 children who became research subjects in the development of religious values ​​can be seen in the prayer command there are 6 children (40%) in the BSB category, 6 children (40%) in the BSH category, 3 children (20%) in the MB category, and there are no children (0%) in the BB category. Introducing houses of worship, there were no children (0%) in the BSB category, 8 children (53.33%) in the BSH category, 7 children (46.67%) in the MB category, and no children (0%) in the BB category. Good and bad behavior 5 children (33.33%) in the BSB category, 9 children (60%) in the BSH category, 1 child (6.67%) in the MB category, and no child (0%) in the BB category. It can be concluded that the application of story telling has developed as expected, and there is a role for story telling in the development of children's religious values ​​in Group B TK Alkhairaat Tondo Kec. Mantikulore. From the first week to the fourth week there has been an increase in all aspects observed.